2016
DOI: 10.1111/lang.12214
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Mindsets, Interactional Behaviors, and L2 Development: An Affective‐Social‐Cognitive Model

Abstract: This classroom‐based study explored links among second language (L2) learners’ interaction mindsets, interactional behaviors, and L2 development in the context of peer interaction. While peer interaction research has revealed that certain interactional behaviors (e.g., receiving corrective feedback and engaging in collaborative interaction) assist L2 learning, it is yet unknown why some learners exhibit these interactional behaviors or how learners’ affective states impact their L2 development. The participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 96 publications
(57 citation statements)
references
References 81 publications
2
53
0
2
Order By: Relevance
“…Only a few variables have been investigated, and these with only a handful of studies. In general, learner psychology requires further research as the way in which L2 learners approach communicative tasks may influence their interaction behaviour and determines the ultimate benefit of interaction (Sato 2016). Furthermore, individual differences such as personality and learning styles can reasonably be assumed to influence interaction (Dewaele 2017).…”
Section: Individual Differencesmentioning
confidence: 99%
“…Only a few variables have been investigated, and these with only a handful of studies. In general, learner psychology requires further research as the way in which L2 learners approach communicative tasks may influence their interaction behaviour and determines the ultimate benefit of interaction (Sato 2016). Furthermore, individual differences such as personality and learning styles can reasonably be assumed to influence interaction (Dewaele 2017).…”
Section: Individual Differencesmentioning
confidence: 99%
“…Empirical studies have investigated whether these learning opportunities occur when L2 speakers engage in communicative tasks. Several studies have focused on interactional feedback and learner responses and reported positive associations with L2 development (Adams, ; McDonough, ; Sato, ; Sato & Lyster, ).…”
mentioning
confidence: 99%
“…Les résultats de cette série d'analyses montrent que la plupart du temps : (a) le temps de parole des enseignants éclipse le temps de parole des élèves, (b) les leçons utilisent des exercices mécaniques (par exemple, répétitions, exercices de substitution) comme principale méthode d'enseignement, et les enseignants proposent très peu d'activités favorisant l'implication cognitive, et (c) il y a peu d'activités en groupe/en binôme pour promouvoir la communication. Les résultats obtenus à partir de cette étude sont concordants avec les résultats de nos précédentes études sur l'enseignement de LVE et l'Enseignement d'une Matière par l'Intégration d'une Langue Étrangère 12 (EMILE) (Gabillon et Ailincai, 2013, 2017. Ils montrent que la participation et l'implication cognitive des apprenants peuvent être améliorées si l'enseignant incorpore les éléments suivants dans sa pratique (cf.…”
Section: Discussion Et Conclusionunclassified
“…Les travaux de recherche menés dans la perspective interactionniste utilisent l'analyse des interactions conversationnelles et visent à cerner les liens entre l'interaction de personne à personne et le développement d'une langue étrangère/seconde (Gass, 1986 ;Mackey, 1999 ;McNeil, 2012 ;Philp, 2016 ;Sato, 2017). La perspective interactionniste considère l'apprentissage d'une langue étrangère comme un processus cognitif intra et interpersonnel.…”
Section: Perspective Interactionnisteunclassified